Distinct Mechanism of Cysteine Oxidation-Dependent Activation and Cold Sensitization of Human Transient Receptor Potential Ankyrin 1 Channel by High and Low Oxaliplatin - Miyake, Takahito; Nakamura, Saki; Meng, Zhao; Hamano, Satoshi; Inoue, Keisuke; Numata, Tomohiro; Takahashi, Nobuaki; Nagayasu, Kazuki; Shirakawa, Hisashi; Mori, Yasuo; Nakagawa, Takayuki; Kaneko, Shuji (Frontiers in Physiology, 2017)
Oxaliplatin, a third-generation platinum-based chemotherapeutic agent, displays unique acute peripheral neuropathy triggered or enhanced by cold, and accumulating evidence suggests that transient receptor potential ankyrin 1 (TRPA1) is responsible. TRPA1 is activated by oxaliplatin via a glutathione-sensitive mechanism. However, oxaliplatin interrupts hydroxylation of a proline residue located in the N-terminal region of TRPA1 via inhibition of prolyl hydroxylase (PHD), which causes sensitization of TRPA1 to reactive oxygen species (ROS). Furthermore, PHD inhibition endows cold-insensitive human TRPA1 (hTRPA1) with ROS-dependent cold sensitivity. Since cysteine oxidation and proline hydroxylation regulate its activity, their association with oxaliplatin-induced TRPA1 activation and acquirement of cold sensitivity were investigated in the present study. A high concentration of oxaliplatin (1 mM) induced outward-rectifier whole-cell currents and increased the intracellular Ca2+ concentration in hTRPA1-expressing HEK293 cells, but did not increase the probability of hTRPA1 channel opening in the inside-out configuration. Oxaliplatin also induced the rapid generation of hydrogen peroxide, and the resultant Ca2+ influx was prevented in the presence of glutathione and in cysteine-mutated hTRPA1 (Cys641Ser)-expressing cells, whereas proline-mutated hTRPA1 (Pro394Ala)-expressing cells showed similar whole-cell currents and Ca2+ influx. By contrast, a lower concentration of oxaliplatin (100 μM) did not increase the intracellular Ca2+ concentration but did confer cold sensitivity on hTRPA1-expressing cells, and this was inhibited by PHD2 co-overexpression. Cold sensitivity was abolished by the mitochondria-targeting ROS scavenger mitoTEMPO and was minimal in cysteine-mutated hTRPA1 (Cys641Ser or Cys665Ser)-expressing cells. Thus, high oxaliplatin evokes ROS-mediated cysteine oxidation-dependent hTRPA1 activation independent of PHD activity, while a lower concentration induces cold-induced cysteine oxidation-dependent opening of hTRPA1 via PHD inhibition.